Specific identification and quantification of circular RNAs from sequencing data - Cheng, Jun; Metge, Franziska; Dieterich, Christoph (Bioinformatics, 2016)
Abstract. Motivation: Circular RNAs (circRNAs) are a poorly characterized class of molecules that have been identified decades ago. Emerging high-throughput se
Advance Access Publication Date: 9 November 2015
Gesehen am 30.04.2020